1996
DOI: 10.1002/j.1460-2075.1996.tb00755.x
|View full text |Cite
|
Sign up to set email alerts
|

The ABC transporter proteins Pat1 and Pat2 are required for import of long-chain fatty acids into peroxisomes of Saccharomyces cerevisiae.

Abstract: Peroxisomes of Saccharomyces cerevisiae are the exclusive site of fatty acid beta‐oxidation. We have found that fatty acids reach the peroxisomal matrix via two independent pathways. The subcellular site of fatty acid activation varies with chain length of the substrate and dictates the pathway of substrate entry into peroxisomes. Medium‐chain fatty acids are activated inside peroxisomes hby the acyl‐CoA synthetase Faa2p. On the other hand, long‐chain fatty acids are imported from the cytosolic pool of activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
272
1
18

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(299 citation statements)
references
References 31 publications
8
272
1
18
Order By: Relevance
“…For ABC transporters such as Ste6p, Atmp1p, and Pxa1p/ Pxa2p, the physiological substrates have been identified [23][24][25]42,51]. As for PDR transporters, detoxification remains as one of the most plausible physiological function, since they General TF and other Ngg1p Inhibition of Pdr1p activity [66,67] PDR, pleiotropic drug resistance; TF, transcription factor.…”
Section: The Physiological Role Of Abc Proteins In S Cerevisiaementioning
confidence: 99%
“…For ABC transporters such as Ste6p, Atmp1p, and Pxa1p/ Pxa2p, the physiological substrates have been identified [23][24][25]42,51]. As for PDR transporters, detoxification remains as one of the most plausible physiological function, since they General TF and other Ngg1p Inhibition of Pdr1p activity [66,67] PDR, pleiotropic drug resistance; TF, transcription factor.…”
Section: The Physiological Role Of Abc Proteins In S Cerevisiaementioning
confidence: 99%
“…Rather than being full transporters such as cystic fibrosis transmembrane regulator (CFTR, ABCC7) or the multidrug resistance gene (MDR1, ABCB1), the peroxisomal ABCDs are half-size transporters and need to homo or heterodimerize to become functional. ABCDs are thought to be involved in the transport of fatty acids, based on three principal findings: 1) peroxisomal membranes are not freely permeable, the entrance and exit of metabolites requires the presence of peroxisomal transporter proteins; 2) the two peroxisomal ABC transporters of Saccharomyces cerevisiae, Pxa1 and Pxa2, form functional heterodimers that transports long-chain fatty acyl-CoAs into the peroxisome (20,63); and 3) inactivation of ABCD1 causes the human disease X-linked adrenoleukodystrophy (X-ALD), which is biochemically characterized by the pathognomonic accumulation of saturated VLCFAs, mainly hexacosanoic acid (C26:0), in plasma and tissues. Oxidation of the VLCFA C26:0 and C24:0 is impaired in X-ALD fibroblasts, suggesting that ABCD1 is involved in the import of VLCFAs into the peroxisome for degradation (45).…”
mentioning
confidence: 99%
“…The data demonstrate that the PHA monomer composition is strongly dependent on the externally fed fatty acids. When C 10 fatty acids were used as the carbon source, C 10 PHA accounted for about 72% of the total biopolymer while no C 12 PHA was detected. Similarly, recombinant yeast grown on tridecanoic acid (C 13 ) and undecanoic (C 11 ) acid produced PHAs containing odd-chain monomers ranging from C 13 to C 7 , with the major monomer components being C 13 and C 11 PHAs.…”
Section: Resultsmentioning
confidence: 99%
“…This creates a window where they may be temporarily active in the cytosol. In some studies, 15 to 25% of the ␤-oxidation enzyme activities were found in the cytosol of yeast (6,10,14,26). This explains why wild-type yeast can synthesize PHA in the cytosol and why PHA synthesized in wild-type yeast and the pex5 mutants contains PHA monomers with C backbones different in length than the fed fatty acids.…”
Section: Discussionmentioning
confidence: 99%